Taxes and Sustainability: Integrating Financial and Ecological Aspects into Strategic Management - Muhammad Yamin Noch; Mohammad Ridwan Rumasukun (Golden Ratio of Taxation Studies, 2024)
This qualitative research explores the intricate relationship between income tax policies and work motivation from multiple perspectives, including economic, psychological, sociological, and organizational behavior. The study aims to understand how income tax policies influence employees' attitudes, behaviors, and perceptions within organizational settings. The research methodology involves a systematic literature review and thematic analysis of existing scholarly literature. Data collection entails comprehensive searches of electronic databases and manual searches of bibliographies to identify relevant sources. The data analysis process involves iterative cycles of reading, coding, and thematic synthesis to identify patterns, themes, and theoretical insights embedded within the literature. The results reveal that income tax policies have multifaceted impacts on work motivation, shaping employees' attitudes, behaviors, and organizational dynamics. From an economic perspective, taxation policies influence labor supply, turnover rates, and compensation expectations. From a psychological standpoint, taxation policies impact employees' perceptions of fairness, autonomy, and control. Sociologically, taxation policies reflect broader societal values and power dynamics, shaping organizational culture and employee experiences. The findings underscore the importance of aligning taxation policies with organizational values and objectives to promote a culture of fairness, equity, and inclusivity within the organization. Transparent communication about taxation policies and their implications for compensation and benefits is essential for fostering a positive work environment conducive to motivation and performance.